Metal-anchoring, metal oxidation-resistance, and electron transfer behavior of oxygen vacancy-rich TiO2 in supported noble metal catalyst for room temperature HCHO conversion - Ahmad, Waleed; Jeong, Hochan; Nahm, Ho-Hyun; Lee, Yeunhee; Park, Eunseuk; Lee, Heehyeon; Ali, Ghulam; Kim, Yong-Hyun; Jurng, Jongsoo; Oh, Youngtak (Elsevier BV, 2023)
Thermal catalytic oxidation at room temperature using a noble metal catalyst is a rapid, stable, and efficient removal strategy for HCHO, a ubiquitous indoor air pollutant. However, the catalytic oxidation optimization through the support defect control has been barely explored. We prepared an oxygen vacancy-rich anatase TiO2 (VO-TiO2) as electron transfer catalyst support for the efficient catalytic conversion of HCHO to CO2 and H2O. VO- TiO2, prepared by chemical vapor condensation with post heat treatment, exhibits void-embedded nano -structures and electron paramagnetic activity, which governs the deposition pattern of Pt nanoparticles upon the impregnation. Pt/VO-TiO2 (0.086 wt% Pt) converted 100% of 10 ppm HCHO at room temperature and 200,000 cm(3) h(-1) gcat (-1) GHSV in >250 min. The X-ray absorption (XAS) studies of used catalysts confirmed the conservation of metallic state of Pt only in oxygen vacancy-rich anatase TiO2 (VO-TiO2). The First-principles density-functional theory calculations revealed that the excess electrons at the oxygen vacancies in VO-TiO2 stabilize the otherwise -vulnerable Pt nanoparticles. This study demonstrates an effective defect control strategy for transforming a TiO2 support into a dynamic electron transfer catalyst platform.